2020
DOI: 10.1042/bst20191108
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome view of a killer: African swine fever virus

Abstract: African swine fever virus (ASFV) represents a severe threat to global agriculture with the world's domestic pig population reduced by a quarter following recent outbreaks in Europe and Asia. Like other nucleocytoplasmic large DNA viruses, ASFV encodes a transcription apparatus including a eukaryote-like RNA polymerase along with a combination of virus-specific, and host-related transcription factors homologous to the TATA-binding protein (TBP) and TFIIB. Despite its high impact, the molecular basis and tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 117 publications
1
38
0
Order By: Relevance
“…Some studies have also shown that the transcription mechanisms of ASFV and VACV are host -independent and similar to the transcription of certain yeast plasmid-encoded toxin genes. These results suggest that the NCLDV family and the killer plasmids share a common evolutionary pathway (37). While studying ASFV transcription termination by the third NGS, a polyU termination motif has been detected in the RNA of approximately 2/3 of early and late genes, but not in nearly 1/3 of the RNA.…”
Section: Transcriptionmentioning
confidence: 91%
See 2 more Smart Citations
“…Some studies have also shown that the transcription mechanisms of ASFV and VACV are host -independent and similar to the transcription of certain yeast plasmid-encoded toxin genes. These results suggest that the NCLDV family and the killer plasmids share a common evolutionary pathway (37). While studying ASFV transcription termination by the third NGS, a polyU termination motif has been detected in the RNA of approximately 2/3 of early and late genes, but not in nearly 1/3 of the RNA.…”
Section: Transcriptionmentioning
confidence: 91%
“…Although replication of ASFV mainly occurs in the VF in the cytoplasm, there is also a brief moment in the nucleus for duplication in the early stage. After 8-16 h, mid- and late-stage genes begin to express to synthesize structural proteins required to form nascent virus and early transcription factors packaged in the virus particles ( 7 , 37 ). Studies have shown that there are 68 types of viral proteins through mass spectrometry analysis, including structural proteins and non-structural, which are indispensable for virus transcription, DNA repair, and protein modification ( 38 ).…”
Section: Asfv Infection Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…African Swine Fever Virus (ASFV) also encodes a vRNAP with subunits exhibiting homology to RNAPII subunits and TBP. One of the subunits also exhibits remarkable structural and functional similarities to TFIIB (Cackett et al, 2020). For such viruses like vaccinia virus and ASFV, which assemble a viral PIC using a vRNAP complex, the critical usage of host TFIIB is bypassed, as they have evolved TFIIB-like proteins.…”
Section: Viruses Have Evolved Proteins Similar To Tfiibmentioning
confidence: 99%
“…The interaction of viral transcriptional regulators with TFIIB is therefore critical for transcription of protein-coding genes in a number of viruses. TFIIB has proven to be an important protein in viral transcription to such an extent that some viruses have evolved to possess proteins with structures similar to TFIIB in order to effectively transcribe their genes (Grimm et al, 2019;Cackett et al, 2020). Evidence suggests that TFIIB is not only intricately linked to viral pathogenesis, but is also selectively targeted by viruses to sustain viability.…”
Section: Introductionmentioning
confidence: 99%